2020
DOI: 10.1093/mnras/staa206
|View full text |Cite
|
Sign up to set email alerts
|

Variable stars in the Sh 2-170 H ii region

Abstract: We present multi-epoch deep (∼20 mag) I c band photometric monitoring of the Sh 2-170 star-forming region to understand the variability properties of pre-main-sequence (PMS) stars. We report identification of 47 periodic and 24 non-periodic variable stars with periods and amplitudes ranging from ∼4 hrs to 18 days and from ∼0.1 to 2.0 mag, respectively. We have further classified 49 variables as PMS stars (17 Class ii and 32 Class iii) and 17 as main-sequence (MS)/field star variables. A larger fraction of MS/f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 72 publications
0
4
0
1
Order By: Relevance
“…In 1945, Joy (1945) observed photometric variability of up to 3 mag for 11 T Tauri stars, of which five are also part of this study (R CrA, S CrA, RU Lup, T Tau, RY Tau). Over recent decades it has turned out that variability in the X-ray to mid-infrared wavelength range is common for pre-main sequence stars (e.g., Sinha et al 2020;Guarcello et al 2019;Robinson & Espaillat 2019;Rice et al 2015;Venuti et al 2015;Kóspál et al 2012). Recent infrared observations of several clusters with the Spitzer Space Telescope at 3.6 and 4.5 µm revealed that typically more than half of the pre-main sequence stars show significant temporal variations (e.g., Serpens South: ∼70%, NGC 1333: ∼50%, GGD 12-15: ∼85%, CSI 2264: ∼90%; Wolk et al 2018Wolk et al , 2015Rebull et al 2015;Cody et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In 1945, Joy (1945) observed photometric variability of up to 3 mag for 11 T Tauri stars, of which five are also part of this study (R CrA, S CrA, RU Lup, T Tau, RY Tau). Over recent decades it has turned out that variability in the X-ray to mid-infrared wavelength range is common for pre-main sequence stars (e.g., Sinha et al 2020;Guarcello et al 2019;Robinson & Espaillat 2019;Rice et al 2015;Venuti et al 2015;Kóspál et al 2012). Recent infrared observations of several clusters with the Spitzer Space Telescope at 3.6 and 4.5 µm revealed that typically more than half of the pre-main sequence stars show significant temporal variations (e.g., Serpens South: ∼70%, NGC 1333: ∼50%, GGD 12-15: ∼85%, CSI 2264: ∼90%; Wolk et al 2018Wolk et al , 2015Rebull et al 2015;Cody et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The period detected in the quiescent LC of the Gaia 20eae might correspond to the rotational period of the star. This type of period is commonly observed in Class ii/iii type of YSOs as shown by Sinha et al (2020). Figure 3 shows the phase folded LC of the Gaia 20eae during its quiescent phase.…”
Section: Light Curvementioning
confidence: 57%
“…Figure 3 shows the phase folded LC of the Gaia 20eae during its quiescent phase. The amplitude of variation is of the order of 0.2 mag which is also typical of Class ii/iii type of YSOs (Sinha et al 2020).…”
Section: Light Curvementioning
confidence: 75%
“…We have used the Gaia proper motion (PM) data with σ P M <3 mas/yr to determine the membership probability of the stars belonging to the NE-cluster found in the S301 region using the method described in Balaguer-Núnez et al (1998). This method has been extensively used recently (for example, Sinha et al 2020;Sharma et al 2020;Kaur et al 2020;Pandey et al 2020b). PMs in RA and Dec are plotted as vector-point diagrams (VPDs) in the top panels of Figure 4.…”
Section: Membership Probability Of Stars In the Ne Clustermentioning
confidence: 99%